Corporate performance analysis an empirical evidence from Indian equity market - Anish Sebastian (My University, 2025)
The study provides a comprehensive analysis of the determinants of corporate performance among non-financial corporations listed in the Indian equity market. The research focuses on key financial performance metrics such as Return on Capital Employed (ROCE), Return on Assets (ROA) and Return on Equity (ROE) to understand the impact of significant attributes such as firm size, capital structure, liquidity, tangibility, growth rate, business risk and firm age. The analysis is conducted across 100 top performing firms, representing ten major sectors such as Automobile, FMCG, Healthcare, IT, Media, Metal, Pharma, Realty, Consumer Durables and Oil & Gas. These firms were selected based on their weightage in Nifty indices, ensuring a comprehensive representation of sectoral performance in the Indian financial market. The study adopts advanced econometric techniques, including panel data regression models, fixed and random effects analysis and dummy variable, to account for both sectoral variations and temporal changes over two distinct periods as before and after 2014. The segmentation captures the economic, regulatory and structural transformations in the Indian market, particularly those introduced after 2014. By comparing pre- and post-reform periods, the research provides refined insights into how these transformations influenced corporate strategies and financial outcomes. Empirical results reveal significant correlations between the studied attributes and corporate performance metrics, with notable sectoral differences. Factors such as firm size, capital structure and tangibility show strong relationships with ROCE, ROA and ROE, while temporal analysis highlights shift in corporate performance influenced by regulatory reforms and market dynamics. The findings underscore the crucial role of key determinants in driving financial efficiency and profitability. This study contributes to the academic discourse by offering a sector-specific and temporal understanding of corporate performance in the Indian non-financial sector. Its practical implications extend to corporate managers, policymakers and investors, providing practical insights for optimising financial strategies, improving operational efficiency and fostering sustainable growth in a rapidly evolving economic environment.
Keywords: Corporate performance; Indian equity market; non-financial corporations; ROCE; ROA; ROE; sectoral analysis; panel data regression; regulatory reforms; temporal analysis.